Effects of retinoic acid receptor α modulators on developmental ethanol-induced neurodegeneration and neuroinflammation - Saito, Mariko; Subbanna, Shivakumar; Zhang, Xiuli; Canals-Baker, Stefanie; Smiley, John F.; Wilson, Donald A.; Das, Bhaskar C. (Frontiers in Neuroscience, 2023)
Ethanol exposure in neonatal mice induces acute neurodegeneration followed by long-lasting glial activation and GABAergic cell deficits along with behavioral abnormalities, providing a third trimester model of fetal alcohol spectrum disorders (FASD). Retinoic acid (RA), the active form of vitamin A, regulates transcription of RA-responsive genes and plays essential roles in the development of embryos and their CNS. Ethanol has been shown to disturb RA metabolism and signaling in the developing brain, which may be a cause of ethanol toxicity leading to FASD. Using an agonist and an antagonist specific to RA receptor α (RARα), we studied how RA/RARα signaling affects acute and long-lasting neurodegeneration and activation of phagocytic cells and astrocytes caused by ethanol administered to neonatal mice. We found that an RARα antagonist (BT382) administered 30 min before ethanol injection into postnatal day 7 (P7) mice partially blocked acute neurodegeneration as well as elevation of CD68-positive phagocytic cells in the same brain area. While an RARα agonist (BT75) did not affect acute neurodegeneration, BT75 given either before or after ethanol administration ameliorated long-lasting astrocyte activation and GABAergic cell deficits in certain brain regions. Our studies using Nkx2.1-Cre;Ai9 mice, in which major GABAergic neurons and their progenitors in the cortex and the hippocampus are labeled with constitutively expressed tdTomato fluorescent protein, indicate that the long-lasting GABAergic cell deficits are mainly caused by P7 ethanol-induced initial neurodegeneration. However, the partial reduction of prolonged GABAergic cell deficits and glial activation by post-ethanol BT75 treatment suggests that, in addition to the initial cell death, there may be delayed cell death or disturbed development of GABAergic cells, which is partially rescued by BT75. Since RARα agonists including BT75 have been shown to exert anti-inflammatory effects, BT75 may rescue GABAergic cell deficits by reducing glial activation/neuroinflammation.